Lipid-Binding Aegerolysin from Biocontrol Fungus Beauveria bassiana - Nada Kraševec; Anastasija Panevska; Špela Lemež; Jaka Razinger; Kristina Sepčić; Gregor Anderluh; Marjetka Podobnik (Toxins, 2021)
Fungi are the most common pathogens of insects and thus important regulators of their populations. Lipid-binding aegerolysin proteins, which are commonly found in the fungal kingdom, may be involved in several biologically relevant processes including attack and defense against other organisms. Aegerolysins act alone or together with membrane-attack-complex/perforin (MACPF)-like proteins to form transmembrane pores that lead to cell lysis. We performed an in-depth bioinformatics analysis of aegerolysins in entomopathogenic fungi and selected a candidate aegerolysin, beauveriolysin A (BlyA) from Beauveria bassiana. BlyA was expressed as a recombinant protein in Escherichia coli, and purified to further determine its functional and structural properties, including lipid-binding ability. Aegerolysins were found to be encoded in genomes of entomopathogenic fungi, such as Beauveria, Cordyceps, Metarhizium and Ophiocordyceps. Detailed bioinformatics analysis revealed that they are linked to MACPF-like genes in most genomes. We also show that BlyA interacts with an insect-specific membrane lipid. These results were placed in the context of other fungal and bacterial aegerolysins and their partner proteins. We believe that aegerolysins play a role in promoting the entomopathogenic and antagonistic activity of B. bassiana, which is an active ingredient of bioinsecticides.